ANALYSIS OF INCOME OF RICE FARMERS IN GUGUAK KURANJI HILIR VILAGE SUNGAI LIMAU DISTRICT PADANG PARIAMAN REGENCY - RAHAYU, TESA; Juita, S.Pd. M.Si, Erna; Zuriyani, M.Si, Elvi (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ Based of arean production rice in Guguak Kuranji Hilir vilage Sungai Limau district Padang PariamanÂ regency, have many problems faced by the farmers, when the moment arrives with the result that they are still very abundant but their income still low. This study aims to determine, analyze and discuss the cost of farmers, farmer acceptance, profit/income of farmers and the R/C ratio of lowland rice farmers in a time period of planting.This study includes research into âquantitative descriptiveâ is a method in researching the status of a group of people, an object, a set of conditions, a system ofÂ thought or aclass of events in the present. This study aims to create a description, picture, or drawing of the respondents systematically with a view to understand and predict the behavior of some aspects of the observed population. The populations of study are rice farmer who are in Guguak Kuranji Hilir vilage Sungai Limau district Padang Pariaman regency, and 5 samples contained area surroundings are Pasar Paingan 16 households, Siguruang 18 households, Sarang Alang 23 households, Kampung Pisang 24 households and 25 familiesin Bukit Jaring Padang Jambu with Proportional Random Sampling.Based on the results of data analysis of the obtained results of the studyâs findings that: (1) the cost of rice farmers is Rp. 2.521.151. (2) Acceptance of rice farmers is 4.535.788 per ton/ha (3) gain / profit of rice farmers Rp. 2.014.637. (4) R/C ratio of rice farmers Rp. 1,1. Feasibility rice field farming carried on in Guguak Kuranji Hilir vilage can be determined by using the Analysis Revenue Cost Ratio (R/C) ratio, which is the ratio between receipts (revenue) and expenses (cost). It can be concluded that rice farming in rice fields in Guguak Kuranji Hilir vilage Sungai Limau district Padang Pariaman regency less feasible to be developed because when compared to the every day needs of the community such as the cost of living, school fees etc. It is not sufficient with the advantage that only 0,1.